Continuous improvements in short and long-term outcomes after partial hepatectomy for hepatocellular carcinoma in the 21st century: Single institution experience with 1300 resections over 18 years. (September 2021) - Goh, Brian K.P.; Chua, Darren W.; Koh, Ye-Xin; Tan, Ek-Khoon; Kam, Juinn-Huar; Teo, Jin-Yao; Cheow, Peng-Chung; Jeyaraj, Prema Raj; Chow, Pierce K.H.; Chan, Chung-Yip; Chung, Alexander Y.F.; Ooi, London L.P.J.
Abstract: Introduction: To investigate the changing trends in short- and long-term outcomes after partial hepatectomy(PH) for hepatocellular carcinoma(HCC) performed in the 21st century. Methods: A retrospective review was conducted on 1300 consecutive patients who underwent PH for HCC. The study cohort was divided into 3 time periods(P): P1(2000–2005), P2(2006–2011) and P3(20012-2017). Results: Comparison between the patients' baseline demographic features across the 3 periods demonstrated that patients were significantly older, had decreasing frequency of hepatitis B, increasing non-alcoholic fatty liver disease, lower alpha-feto protein(AFP) level, lower creatinine levels, less likely to undergo emergency surgery, less likely to undergo major hepatectomy, more likely to undergo repeat resection and minimally-invasive surgery. There was also an increase in operation time, decrease in blood loss, increase frequency in the use of Pringles manoeuvre, decrease liver failure, decrease length of stay and decrease postoperative mortality. HCC resected were of smaller size, less likely to demonstrate microvascular invasion and less likely to have close margins. This was associated with significant improvement in overall survival and recurrence free interval over time. Period of resection was an independent predictor of 90-day mortality and OS on multivariate analysis. Conclusion: We observed a continuous improvement in postoperative outcomes including postoperative mortality and long-term survival after PH for HCC over the past 18 years. Highlights: Over the past 18 years, we observed an increase in the number of PH for HCC performed at our institution. In tandem with this, there was a continuous improvement in postoperative outcomes including postoperative mortality and long-term survival after PH for HCC. The importance of these findings is that it suggest that improvement in patient selection, refinement in surgical management and advancements in palliative treatments have led to overall improvements in the outcomes of patients after PH for HCC.